Five years of implementing the United Nations Programme of Action on Small Arms and Light Weapons : regional analysis of national reports - Kytömäki, Elli (United Nations Institute for Disarmament Research, 2006)
This publication analyzes the information contained in national reports voluntarily submitted by states on their implementation of the United Nations Program of Action on Small Arms and Light Weapons from 2002 to 2005. To date, 137 countries have participated in national reporting, which indicates a growing awareness across the globe on problems related to the illicit trade in small arms and light weapons. However, the level of implementation in different regions remains unequal, and while the number of reporting states is increasing in most regions, the level of reporting and of implementation remain low in some regions.--Publisher's description.